An Analysis of Address Term Used in Indonesian (Bali) Kinship and English Kinship System - Pande Ayuk Septiari (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This research investigates the address term used in Balinese kinship and English kinship, and show how they different. Society cannot be separated from doing interaction to each other through communicate using the language. Address term is commonly use in communication to address the interlocutor, such as families and relatives. This study uses descriptive qualitative approach. The data is focused on the address term use in kinship system in Bali and compare to English Kinship. The data of Balinese kinship are collected by observing the daily communication in the society and also conduct an interview to fifteen participants, while English kinship data were taken from previous researches. The result of this study show that Balinese kinship has many address terms in kinship system that differentiated by each caste, and Balinese kinship is more complex than English kinship.